2004
DOI: 10.1590/s1678-77572004000100013
|View full text |Cite
|
Sign up to set email alerts
|

Pool of bovine morphogenetic proteins and guided tissue regeneration in the treatment of intrabony periodontal defects: I- Clinical measurements

Abstract: he purpose of this study was to evaluate the effect of the pool of bovine BMPs on the treatment of intrabony defects. The sample comprised 15 patients aged 26 to 57 years old presenting with 10 pairs of lesions of 2 or 3 walls or 2-3 walls ³5mm, located in the same type teeth (premolar or molar) and same jaw. The test defects were treated with combination of a pool of bovine bone morphogenetic and resorbable hydroxyapatite carrier (BMPs-HA), bovine demineralized bone matrix (MB) and coverage by a bovine collag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
0
10
0
1
Order By: Relevance
“…In this study, we utilized Wistar rats as the experimental model, considering the positive bone tissue response characteristics in this mammal, which resemble those found in humans, and also the ease of acquiring and handling these animals. 7,8,10,11 When the animals in this study were analyzed on the seventh day after creating the bone defects, it was observed that Group 1 (treated with laser associated with BMPs) was at a more advanced stage of repair than the other groups studied, presenting an area of vessel neoformation, neoformed bone tissue with a large concentration of osteoblasts and absence of inflammatory reaction. On the other hand, in the other groups the presence of inflammatory reaction and necrosed tissue (Group 4 only) was very evident.…”
Section: Discussionmentioning
confidence: 89%
“…In this study, we utilized Wistar rats as the experimental model, considering the positive bone tissue response characteristics in this mammal, which resemble those found in humans, and also the ease of acquiring and handling these animals. 7,8,10,11 When the animals in this study were analyzed on the seventh day after creating the bone defects, it was observed that Group 1 (treated with laser associated with BMPs) was at a more advanced stage of repair than the other groups studied, presenting an area of vessel neoformation, neoformed bone tissue with a large concentration of osteoblasts and absence of inflammatory reaction. On the other hand, in the other groups the presence of inflammatory reaction and necrosed tissue (Group 4 only) was very evident.…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, other carriers that produced better results must be used for testing the pBMPs studied here. The use of a membrane barrier associated or not associated with osteoinductive materials is a current procedure in dentistry 25,26 . Also, it has been used in orthopedic surgery 13,27 , being a center of interest in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that its presence was not seen histologically at 30 days after surgery in both treatments. Collagen membrane has shown satisfactory results in dentistry 25,26 and in treatment of nonsegmental defects experimentally produced in flat bones of several laboratory animals 18,28 . Despite that, in segmental defects, there is a need for better controlled studies to establish the membrane influence in bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…Quando se associa a BMP com um carreador, propicia-se imobilidade da proteína na área, diminui-se a quantidade de BMP necessária e o tempo para que ocorra a indução 45 . Dentre os materiais testados em associação à BMP, ressaltamos: hidroxiapatita 35,46 ; esponjas de colágeno reabsorvível 16,21,25,35,[46][47][48] ; politetrafluoretileno expandido 49,50 ; osso bovino 16,21,[51][52][53][54] e osso autógeno 55 . Os carreadores mais utilizados são a hidroxiapatita e o colágeno, pois são compostos presentes na estrutura óssea, absorvendo naturalmente a BMP 56 .…”
Section: Revisão De Literaturaunclassified